Genuine Movement Learning Through a Deleuzian Approach - Larsson, Håkan; Nyberg, Gunn; Barker, Dean (Frontiers in Sports and Active Living, 2021)
The purpose of the article is to outline how Deleuzian concepts, notably the notions of apprenticeship based on a pedagogy of the concept, can stimulate thinking and understanding of movement learning, and provide insights about pedagogical implications in various movement educational settings. Methodologically, the article falls somewhere in between theoretical exposition and presentation of original empirical research, i.e., a ‘theoreticoempirical’ exposition. We borrowed some ideas formulated by Deleuze (and Guattari), which have been further developed by educational researchers, about ‘an apprenticeship in signs’ based on ‘a pedagogy of the concept’, to analyse situations where students explore new movements. We use material generated from pedagogical interventions comprising of exploration of kinescapes. In these interventions, school and university students are encouraged to explore, and learn, juggling, unicycling and dancing. Findings indicate how students pass through interpretative illusions until some of them grasp difference in itself in what could be called its immanent differentiation of the actual, i.e., they learn how to juggle, unicycle or dance. This is what we designate genuine learning. The triadic relation between concepts, percepts and affects offer us clues to what juggling, unicycling or dancing mean to learners (concepts), what learners pay attention to while practising (percepts), and what gets them moving (affects). Importantly, through viewing learning as an apprenticeship in signs, the Deleuzian approach reminds us that the triadic relation is open-ended, meaning that concepts, percepts and affects are never final but always a potential actualisation. Concepts, percepts and affects are constantly in the process of becoming. Since genuine learning is not about narrowing down how a movement should be executed and experienced, the task of a movement educator could, then, be to accompany learners in explorative pursuits. In this way, teachers can help learners escape preconceptions about movements (who can do what and when) and instead explore new movement opportunities.